(untitled) (Research, Society and Development, 2020)
Tomato is one of the most consumed vegetables in the world. This work aimed to evaluate post-harvest quality of Italian Saladete tomatoes grown in a protected environment, with different ways of calcium application, in the Middle São Francisco Valley. Consisting of five Italian tomato hybrids (Anjico, Gabrielle, Liberty, Ty 2006 and Shanty), and three different ways of calcium application (T0 without application of calcium; T1 application of calcium in the opening flower, and T2 weekly application of calcium in the fruit). Poductivity, average fruit mass, incidence of apical rot, fruit firmness, soluble solids (SS), titratable acidity (AT), and pH, were analized. The experimental design used was a completely randomized block design in a factorial scheme (five cultivars x three ways of calcium application), with three repetition and using two central plants as useful plot for analysis, except for fruit firmness that was carried out in a completely randomized design, using tree fruits per analysis. According to the results obtained, hybrids of Italian saladete tomatoes behaved in a satisfactory manner, therefore it is recommended to cultivate hybrids of Italian saladete tomatoes in the Middle São Francisco Valley, mainly hybrid Anjico. Calcium application way did not interfere with post-harvest attributes.